ANALISIS PENGARUH RISIKO KREDIT DAN PERMODALAN TERHADAP PROFITABILITAS MELALUI PERTUMBUHAN KREDIT - Manurung, Wanda Valeria; Bintoro, Nugroho Suryo (Contemporary Studies in Economic, Finance and Banking, 2023)
Along with the deceleration of global and domestic economy, the profitability of banks is also decreasing. Such degradation must receive sufficient attention as it can reduce people’s trust and bank’s business sustainability if not addressed properly. The objective of this research is to assess the effects of credit risk and capital on profitability both directly and indirectly through the mediation of credit growth. Using purposive sampling technique, banks member of HIMBARA (Association of State-Owned Banks) from the first quarter of 2012 to the fourth quarter of 2021 were selected as the sample. The data was processed using panel data regression and path analysis. This study finds that NPL and CAR negatively and significantly influence credit growth, that NPL negatively and significantly affects ROA, that CAR and credit growth have no effect on ROA, and that credit growth does not mediate the effects of NPL and CAR on profitability.